Profil Kondisi Fisik Atlet Ukm Bulutangkis Universitas Setia Budhi Rangkasbitung - Dodi Nurhidayat; Lukmanul Hakim; Ahmad Firmansah (Journal on Education, 2024)
This study aims to determine the profile of the physical condition of athletes at UKM badminton at Setia Budhi Rankasbitung University. The physical conditions studied consisted of flexibility, leg power, muscle endurance, abdominal muscle strength, arm muscle strength, balance and reaction speed. This research is a quantitative descriptive research. The population used was all the Badminton UKM athletes at Setia Budhi Rangkasbitung University, totaling 13 athletes. The sample used was 13 athletes. The sampling technique used was total sampling. Data collection instruments used tests and measurements of flexibility (sit and reach), leg power (vertical jump), muscle endurance (wall sit), abdominal muscle strength (sit ups), arm muscle strength (push ups), balance (smart balance test). ), reaction speed (whole body reaction). Data analysis uses descriptive percentages. The results show that the physical condition of the Badminton UKM athletes at Setia Budhi Rangkasbitung University is in the "very poor" category at 0.00% (0 athletes), "poor" at 15.00% (2 athletes), "fair" at 46, 00% (6 athletes), “good” at 38.00% (5 athletes), and “very good” at 0.00% (0 athletes).